Platelet and monocyte activity markers and mediators of inflammation in Takotsubo cardiomyopathy - Pirzer, Rainer L.; Elmas, Elif; Haghi, Dariusch; Lippert, Christiane; Kralev, Stefan Borissov; Lang, Siegfried; Borggrefe, Martin; Kälsch, Thorsten (Heart and vessels, 2012)
Patients with Takotsubo cardiomyopathy (TC) often present with symptoms similar to those of myocardial infarction (MI). We analyzed blood concentrations of mediators of inflammation and platelet- and monocyte-activity markers in patients with TC and MI for significant differences. Clinical data of patients with TC (n = 16) and acute MI (n = 16) were obtained. Serial blood samples were taken at the time of hospital admission (t 0), after 2-4 days (t 1) and after 4-7 weeks (t 2), respectively. Plasma concentrations of interleukin (IL)-6, IL-7, soluble CD40 ligand (sCD40L), and monocyte chemotactic protein 1 (MCP-1) were determined with an ELISA. Tissue factor binding on monocytes, platelet-activation marker CD62P, platelet CD40-ligand (CD40L), and platelet-monocyte aggregates were measured using flow cytometry. Expression of CD62P on platelets and IL-6 plasma levels were significantly lower in patients with TC compared to MI at the time of hospital admission. IL-7 plasma levels were significantly elevated in patients with TC compared to patients with MI at 2-4 days after hospital admission. No significant differences were observed concerning sCD40L and MCP-1 plasma levels, tissue factor binding on monocytes, CD40L expression on platelets, and platelet-monocyte aggregates at any point in time. Our results indicate that inflammatory mediators and platelet-activity markers contribute to the differences in the pathogenesis of MI and TC.